2011
DOI: 10.4155/bio.11.99
|View full text |Cite
|
Sign up to set email alerts
|

Direct Analysis in Real Time Coupled with Dried Spot Sampling for Bioanalysis in a Drug-Discovery Setting

Abstract: The DART-MS/MS method was applied to DBS sampling for PK/TK studies and also for in vitro screening of absorption, distribution, metabolism and excretion properties. The results from the DART-MS/MS approach correlated well with the LC-MS/MS analyses for comparison.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 7 publications
0
38
0
Order By: Relevance
“…The possibility of analysis of dried spots of liquids on a carrier using DART-MS, reported only in two studies [22,23] for spots of milk on paper and for DBS on glass slides, has been confirmed using an HPTLC plate as a porous carrier and the DPS scanning analysis by the DART ion source with an adjustable angle. This gives rise for further studies of dried spots on a flat carrier by DART-MS-used for the confirmation of liquid sample analysis or as an independent analytical method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of analysis of dried spots of liquids on a carrier using DART-MS, reported only in two studies [22,23] for spots of milk on paper and for DBS on glass slides, has been confirmed using an HPTLC plate as a porous carrier and the DPS scanning analysis by the DART ion source with an adjustable angle. This gives rise for further studies of dried spots on a flat carrier by DART-MS-used for the confirmation of liquid sample analysis or as an independent analytical method.…”
Section: Discussionmentioning
confidence: 99%
“…The thirdgeneration DART ion source "DART-SVPA" is capable of being set off axis to the sampling surface for direct surface analyses, giving rise to the studies in scanning surface analysis using DART-MS. Using such a source, the capability of quantitation of several drugs from DBS on glass slides has been proven using a triple quadrupole mass spectrometer in a pharmacokinetic study [23]. To our knowledge, no other studies on DART-MS analysis of dried spots on a carrier have been performed until now.…”
Section: Analysis Of Dried Propolis Spots (Dps)mentioning
confidence: 98%
“…These constraints are greatly relieved by 'microsampling', resulting in the generation of DBS and allowing serial sampling from a strongly reduced amount of laboratory animals, including small rodents such as mice. This allows the replacement of composite pharmaco-or toxicokinetic profiles (obtained from different animals) by serial profiles (obtained within individual animals), which leads to higher data quality ( Clark et al, 2010, Turpin et al, 2010, Crawford et al, 2011. Apart from a large improvement in animal welfare, DBS sampling is also beneficial for the (pharmaceutical) companies involved.…”
Section: Analysis Of Therapeutic Drugs -Toxicokineticsmentioning
confidence: 99%
“…Examples include the automated analysis of DBS, the on-line extraction and analysis of DBS ('direct elution') and direct desorption of DBS (e.g. Crawford et al, 2011, Déglon et al, 2011a. These new developments have recently been reviewed elsewhere (Déglon et al, 2011b, Abu-Rabie, 2011.…”
Section: Analysis Of Therapeutic Drugs -Toxicokineticsmentioning
confidence: 99%
“…[49,74] Another use of DART is the analysis of, covalently bound, organic monolayers on different substrates. [75,76] The application of DART in the field of forensics is not just limited to the detection of (pharmaceutical) drugs from solid samples, [77] plant material, [78] and cotton-swab wipes, [79] DART has also be used to analyze urine samples, [80] dried blood spots, [81] and explosives. [82] Aim of this research…”
Section: Applications Of Dartmentioning
confidence: 99%